Applied Nanotechnologies in Anticoagulant Therapy: From Anticoagulants to Coagulation Test Performance of Drug Delivery Systems - Yuri B. G. Patriota; Luíse L. Chaves; Evren H. Gocke; Patricia Severino; Mônica F. R. Soares; José L. Soares-Sobrinho; Eliana B. Souto (Applied Nano, 2021)
Heparin-based delivery systems have been explored to improve their therapeutic efficacy and to reduce toxicity for different administration routes. Regardless of the applied drug delivery system (DDS), the evaluation of anticoagulant performance is instrumental for the development of a suitable DDS. The understanding of the range of anticoagulant assays, together with their key applications and limitations, is essential both within the context of scientific research and for clinical usage. This review provides an overview of the current anticoagulant therapy and discusses the advantages and limitations of currently available anticoagulant assays. We also discuss studies involving low-molecular-weight heparin (LMWH)-based nanocarriers with emphasis on their anticoagulation performance. Conventional anticoagulants have been used for decades for the treatment of many diseases. Direct oral anticoagulants have overcome some limitations of heparins and vitamin K antagonists. However, the lack of an accurate laboratory assessment, as well as the lack of a factor “xaban” (Xa) inhibitor reversal agent, remains a major problem associated with these anticoagulants. LMWHs represent anticoagulant agents with noteworthy efficacy and safety, and they have been explored to improve their outcomes with various nanocarriers through several administration routes. The main problems related to LMWHs have been surmounted, and improved efficiency may be achieved through the use of DDSs.